Integrating Strategic Management with SDG 10 for Sustainable Development and Equity - Lukita, Chandra; Abdul Rahman, Abdul Wahab; Hikam, Ihsan Nuril; Rahardja, Untung (Pandawan, 2025)
Strategic Management (SM) has traditionally focused on competitive advantage and operational efficiency. However, with the increasing global emphasis on inclusive development, SM now includes addressing systemic issues such as inequality, as outlined in Sustainable Development Goal 10 (SDG 10). This study aims to explore how SM research contributes to SDG 10, focusing on the role of Artificial Intelligence (AI) in advancing equity-driven strategies, specifically in the context of reducing inequalities. A bibliometric analysis was conducted using VOSviewer on 43 Scopus-indexed articles published from 2015 to 2025. This analysis maps global contributions, themes, and AI conceptual integration into SM. The findings show that Spain and the Netherlands are leading contributors in this field. Core themes emphasize governance, Corporate Social Responsibility (CSR), and innovation, while AI is recognized conceptually but lacks empirical integration in reducing inequalities. This study identifies key trends in SM research related to SDG 10 and highlights the need for greater empirical integration of AI in SM. It calls for further research on AI-driven decision-making frameworks that align with equity and sustainability goals.